Genetic admixture history and forensic characteristics of Turkic-speaking Kyrgyz population via 23 autosomal STRs - Pengyu Chen; Xing Zou; Biao Wang; Mengge Wang; Guanglin He (Taylor & Francis Group, 2019)
Kyrgyz people, a Turkic-speaking ethnic group native to Central Asia, are considered as one mixed population from different historical tribes through the processes of conquest, intermarriage, assimilation and migration. The aim of this study was to infer the forensic statistical parameters and genetic structure of Chinese Kyrgyz and explore the patterns of their genetic relationships with adjacent and worldwide reference populations. We genotyped 25 forensic-related markers (amelogenin, Y-indel of rs2032678 and 23 Autosomal Short Tandem Repeats, A-STRs) in 491 Chinese Kyrgyzs. Allele frequency and forensic parameters were calculated using the STRAF software. Pairwise genetic distances were estimated using Phylip and subsequently dissected via principal component analysis, multidimensional scaling plots and phylogenetic relationship reconstruction. Investigations of allele frequency and forensic parameters indicated that all studied A-STRs are informative in the Chinese Kyrgyz population and can be used as a powerful tool in forensic individual identification and parentage testing. Results from genetic relationship analyses demonstrated that Akto Kyrgyz people harbour a genetically close relationship with Turkic-speaking Uyghur and Kazakh. Genetic structure analysis based on the raw genotype data among Eurasian populations further suggested that genetic ancestries and population substructures in Asia are largely associated with language and geography.